REPOSITIONING TEACHING LEARNING ATTITTUDES IN INSTITUTIONAL CONTEXTS AS AN APPROACH TO TECHNOLOGICAL INTERVENTION IN EDUCATION - S. Sailaja Radhakrishna (UICELL, 2021)
Technological interventions for better educational outcomes are well considered notions in the present educational contexts. While teacher training and provision of technological services affirm the ushering in of change, the rural contexts continue to have apprehensions of learning English coupled with the use of technology. Incremental changes requiring far greater adjustments in teaching and learning attitudes are required to formulate an approach to bring in technological intervention. "Technology, when entering the institutional settings of an educational domain, triggers changes in teaching and learning practices (Gill 2009). A contextual approach would act as a motivational strategy to begin the use of devices in the classroom. It is important to identify and investigate factors that play an influential role in technology adoption and capacity building of teachers. Contextual cues can provide language cues which will create opportunities for teaching practices to change for the accommodation of technological intervention. A contextual approach can be initiated by starting with a survey of the needs of learners regarding use of computers and smartphones. Such a survey would also guide a proposal for the capacity building of teachers.